SOLO-Net: A Sparser but Wiser Method for Small Object Detection in Remote-Sensing Images - Lei, Mengqi; Liu, Xianyuan (IEEE geoscience and remote sensing letters, 2024)
Small object detection in remote-sensing images is essential, yet challenging due to the unique characteristics of small objects. On the one hand, it can be difficult to distinguish small objects from complex backgrounds. On the other hand, due to their minuscule size, small objects are also easily submerged during feature fusion. This letter proposes a novel detection method called sparse outlook network (SOLO-Net) to address these issues. First, we propose a top-k sparse outlook (TKSO) attention module and the sparse outlook path aggregation network (SOLO-PAN) as the fundamental component of SOLO-Net. This module improves the performance of the path aggregation network (PANet), thereby enhancing the ability of the model to focus on small objects. Second, we propose a Sigmoid-intersection over union (IoU) loss function specifically designed for small objects, accelerating model convergence and improving detection performance. Finally, we evaluate our model on the RSOD and DIOR datasets, achieving mean average precision (mAP) scores of 93.8% and 74.5%, respectively.